Comparison of blood gas analysis parameters, biochemical tests and hematological parameters in geriatric patients admitted to the emergency department - Ayşegül Bilge; Hatice Şeyma Akça; Abuzer Özkan (National Scientific Medical Center, 2023)
Aim: The primary aim is to compare blood gas parameters (sodium, potassium, glucose, hemoglobin, hematocrit) with biochemical test and hospital hemogram results and thus to investigate the compatibility of blood gas estimation with other laboratory tests in geriatrics. The secondary aim is to compare the effects of these parameters on patient mortality. Material and methods: Patients over the age of 65 who applied to the emergency department were included in our retrospective study. Statistical Package for Social Sciences (SPSS Inc., version 20.0; Chicago, IL) was used for statistical analyzes applying to the emergency department. Statistical significance was accepted as p<0.05. Results: 102 patients were included in our study and 51.97% were male. 9.8% of our patients died. The diagnostic test performance analyzes of BG (blood gas) hemoglobin, hemoglobin, BG hematocrit, hematocrit, BG glucose, glucose, BG sodium, sodium, BG potassium, potassium in predicting mortality revealed with the AUC(area under curve) value being calculated as unsuccessful for BG hemoglobin, hemoglobin, BG hematocrit and hematocrit (AUC value: 0.47, 0.45, 0.46, 0.50). AUC (area under curve) value being calculated as weak for BG glucose, glucose and BG sodium (AUC value: 0.64, 0.61, 0.63 respectively). AUC value being calculated as medium for sodium (AUC value: 0.71). Conclusion: There is no superiority of blood gas parameters over hematological and biochemical parameters in predicting mortality in the geriatric patient group. However, blood gas parameters can be used in patient management as they correlate with other laboratory tests.